The Effect of Capital Structure and Liquidity on Profitability in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange - Seveny Amellia Lingga; Lorina Siregar Sudjiman (Tahta Media Grup, 2026)
This study aims to examine the effect of capital structure and liquidity on the profitability of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023. A quantitative approach was employed, using secondary data from the financial reports of 10 purposively selected companies. Data were analyzed through descriptive analysis, data testing, classical assumption tests, and hypothesis testing. Debt to Equity Ratio (DER) was used to measure capital structure, Current Ratio (CR) was employed to measure liquidity, and Return on Assets (ROA) served as the profitability indicator. The results reveal that DER has a negative yet insignificant effect on ROA. Similarly, CR shows a positive but insignificant influence on ROA. Simultaneously, neither capital structure nor liquidity was found to have a significant effect on profitability.